PENYALURAN KREDIT BANK X AKIBAT PELAKSANAAN NOTA KESEPAHAMAN (MEMORANDUM OF UNDERSTANDING) DENGAN PEGAWAI KONTRAK DI PEMERINTAHAN DAERAH KOTA Y - Yolanda Kurnia Putra; Anggun Lestari Suryamizon; Jasman Nazar (Ensiklopedia of Journal, 2023)
Credit is an inseparable part of the banking world. Various innovations were carried out by the Bank to mobilize and grow credit, one of the innovations carried out by Bank X was to establish a Memorandum of Understanding with City Y Regional Government Agencies or Institutions regarding the implementation of consumption credit facilities for Contract Employees. In the course of the credit, there is a risk that arises, namely default on one of the Contract Employees who resigns or quits. This type of writing is written in the form of empirical juridical research (empirical law research), which can also be called sociological legal research, which is legal research that examines law conceptualized as actual behavior. From the results of the author's research, there are weaknesses in the credit agreement clause in the guarantee or collateral section which places Bank X in a weak position. Based on this, Bank X continues to make persuasive settlement efforts by carrying out good communication, negotiations, and education in order to get an agreement and find a bright spot in the settlement of non-performing loans.